IDENTIFICATION OF CIRCUMSTANCES CONTRIBUTING TO DOMESTIC VIOLENCE: UNDERSTANDING, IMPLEMENTATION - BELYAEVA S.O.; ZASHLYAPIN L.A. (Legal Bulletin)
The relevance of the study of the procedural order of identifying the circumstances that contributed to the commission of domestic violence is associated with the accentuation of this issue in the social sphere, the presence of problems in regulating the procedure for identifying these circumstances and the implementation of information about the identified circumstances. The main goal of the study was to test the hypothesis about the ineffectiveness of the existing practice of crime prevention and the conflict of laws governing the procedure for identifying circumstances that contributed to the commission of crimes. The object area of research is formed by the regulatory provisions of Part 1 and Part 2 of Art. 73 Code of Criminal Procedure of the Russian Federation, part 2 of Art. 158 Code of Criminal Procedure of the Russian Federation, Part 4, Art. 29 Code of Criminal Procedure of the Russian Federation; doctrinal interpretations of relevant legal norms. The methods used in the research were linguistic analysis and the legal-dogmatic method. The conclusions that the co-authors came to as a result of the study are as follows. Identification of the circumstances that contributed to the commission of criminal acts of violence against family members (partnerships) is complicated by general problems of regulatory regulation. The form of response provided by law to the identified circumstances that contributed to this act is not mandatory for the investigator; the methods for implementing the identified information by the investigator are not effective. Similar effectiveness of preventive activities is found in the judicial stages. The court is not obliged to implement the identified circumstances that contributed to domestic violence. The form in which the court implements these circumstances is imitative. Solving the problems of preventing domestic violence within the boundaries of the criminal procedure branch is impossible. To solve such a problem, interdisciplinary or even interdisciplinary research is needed.